Simulation of maturity duration and productivity of two rice varieties under system of rice intensification using DSSAT v 4.5/CERES-Rice model - ANCHAL DASS; AJIT SINGH NAIN; S. SUDHISHRI; SUBHASH CHANDRA (Journal of Agrometeorology, 2012)
Crop growth models have been considered as potential tools for simulating growth and yield of crops. Hence, Decision Support System for Agro-technology Transfer/Crop Estimation through Resource and Environment Synthesis (DSSAT v 4.5/CERES-Rice) model was applied to the data recorded in two years (2008 and 2009). The field experiment included two rice varieties (‘Pant Dhan 4’ and ‘Hybrid 6444’) cultivated with system of rice intensification (SRI) method, under three irrigation schedules (irrigation at 1, 3 and 5 day after disappearance of ponded water) and two planting spacings (20 cm x 20 cm and 25 cm x 25 cm). The model was calibrated using data of 2009 and validated with the data of 2008. For ‘Pant Dhan 4’ maturity was slightly under predicted (gap 2-6 days) by the model with an overall gap between observed and predicted values being 2%, during 2009. However, model predictions were closer (gap 1-2 days) during 2008. The predicted maturity of ‘Hybrid 6444’ was close to the observed one (gap 1 day) but it was over predicted for the year 2008. The model predicted the yield of both the varieties with fair accuracy. The overall gap between predicted and observed yield was 5% for ‘Pant Dhan 4’ and 11.4 % for ‘Hybrid 6444’. Hence the model can be used for predicting maturity and yield of these rice varieties grown with SRI method.